Serum levels of tumour necrosis factor-alpha and interleukin-1 beta during leprosy reactional states. - Sarno, E N (1991)
The possible role of cytokines in leprosy reactions was investigated by analysing the levels of tumour necrosis factor (TNF) and interleukin-1 (IL-1) in serum samples from 39 leprosy patients, 22 of them presenting either type I (upgrading) or type II (ENL) reactions. Fifty per cent of the patients showed elevated concentrations of TNF and IL-1 in at least one of the serum samples tested. This included all four patients undergoing type I reversal reaction and nine (50%) of the ENL patients studied. Concentrations of TNF above 1000 pg/ml were found in four patients with ENL. Development of erythema multiforme in these ENL patients represented an aggravating factor and all four patients suffering from this type of lesion demonstrated increased serum TNF levels. All BT patients tested presented elevated IL-1 levels, while only half of them presented elevated levels of TNF. No correlation was found between any particular systemic symptoms and the levels of TNF and IL-1. These results suggest that TNF and IL-1 may be implicated in leprosy reactions, either acting directly or in synergism with other cytokines.